1992
DOI: 10.1007/bf00023520
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and alkaloid production in Catharanthus roseus, C. trichophyllus and their hybrids

Abstract: Inter and intraspecific variation was analyzed in two Catharanthus species with regard to isozyme polymorphism and indole alkaloid content in roots and leaves. No significant differences in alkaloid production were observed in three groups of C. roseus plants individualized for their flower color. Conversely, comparisons between C. trichophyllus and C. roseus, showed large differences of alkaloid profiles in both roots and leaves. Specific isozyme markers on four presumed loci were found allowing us to establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…roseus) hybrids has been reported in periwinkle (Levy et al 1983, Sevestre-Rigouzzo et al 1993). In the absence of malesterile lines, either the development of pure line cultivars (Levy et al 1983) or the use of micropropagation (Sevestre-Rigouzzo et al 1993) and utilization of the occurrence of high levels of outcrossing due to the absence of intra¯ower self-pollination combined with the use of seedling markers for identifying hybrids have been suggested for exploiting heterosis (Kulkarni 1999). The occurrence of both kinds of pollination in periwinkle thus provides opportunities for developing both pure line and hybrid cultivars, depending on the nature of gene action governing the characters of interest.…”
Section: Discussionmentioning
confidence: 95%
“…roseus) hybrids has been reported in periwinkle (Levy et al 1983, Sevestre-Rigouzzo et al 1993). In the absence of malesterile lines, either the development of pure line cultivars (Levy et al 1983) or the use of micropropagation (Sevestre-Rigouzzo et al 1993) and utilization of the occurrence of high levels of outcrossing due to the absence of intra¯ower self-pollination combined with the use of seedling markers for identifying hybrids have been suggested for exploiting heterosis (Kulkarni 1999). The occurrence of both kinds of pollination in periwinkle thus provides opportunities for developing both pure line and hybrid cultivars, depending on the nature of gene action governing the characters of interest.…”
Section: Discussionmentioning
confidence: 95%
“…Kulkarni et al (1987) reported about the potential of diploids and induced autotetraploids of C. roseus (L.) G. Don in divergent measures of nitrogen and plant spacing (Kulkarni et al 1987). Investigational hybrids have been explained among C. roseus (L.) G. Donand C. trichophyllus (Sevestre-Rigouzzo et al 1993). Levy et al (1983) reported that the considerable heterosis for yields of leaf and root in crosses required three actual lines although heterosis was not revealed for quantity of ajmalicine alkaloid in the roots (Levy et al 1983).…”
Section: Natural and Induced Variationmentioning
confidence: 99%
“…The degree of outcrossing varies with environmental conditions and the presence of seasonal pollinators, mainly butterflies and moths, whereby the floral structure is adapted to pollination by these long-tongued insects [ 29 ]. Self-incompatible strains of MP engage in natural interspecific hybridization which is found to be common locally in Madagascar [ 18 , 30 ]. But in all reality, both types of pollination occur in MP.…”
Section: Geneticsmentioning
confidence: 99%